NEURODEVELOPMENTAL OUTCOME IN PRETERM INFANTS - Palić, Ilija (Medicinski podmladak, 2024)
About 15 million children are born prematurely every year. Preterm delivery is the main cause of death worldwide in children less then five years old. The infants born with very low birth weight (
Keywords: prematurity, brain injury, neurodevelopmental disabilities